Chinese EFL Teachers’ Written Feedback on Expository Argumentation (EA): a Sociocognitive Perspective - Bian, Xiaoyun (Auckland University of Technology, 2018)
Although teacher written feedback on student writing has become a central topic for second language (L2) writing research, investigations into it have mainly focused on the surface-level errors of student writing. This study, situated in the Chinese EFL context where feedback research is more limited, echoed the general call for more research addressing non-error feedback (e.g., organization and content feedback). It was informed by a sociocognitive view of teacher feedback and SFL (Systemic Functional Linguistics) genre pedagogy and followed Hyland and Hyland’s (2006a) lead to study the feedback-and-interpretation process. Particularly, it investigated • how feedback on expository argumentation (EA feedback) is given and processed, as reflected by the teacher’s/student’s decision-making thought processes, and • the extent to which the feedback-and-interpretation process is helpful for student development. Methodologically, the study adopted a case study approach. This approach was used because it is most suitable for answering the research questions explored in the study, that is, the “how” questions about teachers’/students’ decision-making (Bowles, 2010). As a case study, it focused on three teacher-student pairs/cases (a teacher and three of her students) and lasted one semester. To get the best possible answers to research questions, it quantitatively and qualitatively analysed data obtained from think-alouds, teacher comments on student writing, student notes, and interviews (background interviews, retrospective interviews, ongoing interviews, and final interviews). The study found that the teacher consistently provided EA feedback on supporting evidence, cohesion and coherence, topic statement, topic sentences, conclusion, and overall organization and she usually used the following approaches to deliver EA feedback: problems/strengths identifications, explanations, suggestions, revisions, and a combination thereof. The study also found that the students interpreted (accepted and incorporated) EA feedback in different ways and their interpretation of EA feedback was marked by changes. Furthermore, the study found that the teacher’s/students’ decisions to provide/process EA feedback were formed through the workings of the their “mindbodyworld” (Atkinson, 2014). Generally speaking, the study found that the teacher-student interaction during the feedback process did not always go very well, but it was still helpful for the students’ development as writers and feedback receivers. The study was significant in that it advanced the understanding of teacher feedback by providing a sociocognitive explanation about 1) how the teacher offers feedback, 2) how the student attends to teacher feedback, 3) how the teacher, the student, the feedback itself (as the text-level context), and the context interact with each other during the feedback process, and 4) how student learning and development occur during the feedback process. An advanced understanding of teacher feedback had pertinence not only for the Chinese EFL context, but also for other L2 contexts.
Keywords: Teacher feedback on expository argumentation; The feedback-and-interpretation process; Sociognitive theory of learning and development; Chinese EFL context